Effects of argon atoms in excited states on properties of argon-acetylene dusty plasma - Denysenko, I.B.; Ivko, S.; Azarenkov, N.A.; Burmaka, G. (Вопросы атомной науки и техники, 2020)
It is studied how dissociation and ionization of acetylene molecules in their collisions with argon atoms in excited states Ar* may affect properties of argon-acetylene plasma with growing inside of plasma volume dust particles. The study is carried out using a volume-averaged model. To analyze the effects of Ar* atoms on the electron and ion densities, the effective electron temperature and the densities of radical and nonradical neutral species, the values of ionization and dissociation rates for collisions of acetylene molecules with Ar* atoms are varied in numerical calculations. It is found that the collisions of Ar* atoms with acetylene molecules affect essentially the argon-acetylene dusty plasma.